Negation and question in the Leyte- Samar dialect - Caones-Sydiongco, Resurreccion (Tacloban City DWU Graduate School Publication, 1967)
"In this paper some special features of the Leyte-Samar dialect will be treated, viz. the negation and question. Both features are important in the dialect. Besides, the study of the negation may be worthwhile for a comparative study with Cebuano."
Keywords: Waray language